Patient participation in multidisciplinary tumour conferences in breast cancer care (PINTU): a mixed-methods study protocol. Issue 4 (8th April 2019) - Heuser, Christian; Diekmann, Annika; Ernstmann, Nicole; Ansmann, Lena
Abstract : Introduction: A central instrument of multidisciplinary care is the multidisciplinary tumour conference (MTC). In MTCs, diagnosis and treatment of cancer patients are discussed, and therapy recommendations are worked out. As we found previously, patients participate in MTCs in some breast cancer centres in the state of North Rhine-Westphalia, Germany. However, studies on risks and benefits of patient participation have not provided substantiated findings. Therefore, the study's objective is to analyse differences between MTCs with and without patient participation. Methods and analysis: This is an exploratory mixed-methods study. MTCs in six breast and gynaecological cancer centres in North Rhine-Westphalia, Germany, are examined. MTCs will be conducted with and without patient participation. First, interviews with providers concentrating on the feasibility of patient participation and quality of decision-making will be carried out, transcribed and analysed by means of content analysis. Second, videotaped or audiotaped participatory observations in MTCs will be executed. Video data or transcribed audio data from video and audio recordings will be coded using the established "Observational Assessment Rating Scale" for MTCs and analysed by comparing centres with and without patient participation. Third, all patients will fill out a questionnaire before and after MTC, including questions on psychosocial situation, decision-making and expectations before and experiences after MTC. The questionnaire data will be analysed by means of descriptive and multivariate statistics and pre-post-differences within and between groups. Ethics and dissemination: Consultation and a positive vote from the ethics committee of the Medical Faculty of the University of Cologne have been obtained. For all collected data, relevant data protection regulations will be adhered to. All personal identifiers from patients and providers will be pseudonymised, except video recordings. Dissemination strategies include a discussion with patients and providers in workshops about topics such as feasibility, risks and benefits of patient participation in MTCs. Trial registration number: DRKS00012552.